Bibliometric analysis of scientific production on sharing economy. Issue 3 (12th June 2019) - Lima, Sérgio; Carlos Filho, Francisco de Assis
Abstract : Purpose: In recent years, much has been discussed about new consumer practices based on the sharing economy. In this context, the purpose of this paper is to map out the international scientific production on sharing economy. Design/methodology/approach: The research adopted a descriptive qualitative approach. Based on a sample of 95 documents collected in the Scopus database, analyses of bibliometric and sociometric indicators were carried out, as well as content analyses were conducted to identify the main thematic categories in the field. Findings: The results show that sharing economy is an emerging topic, and of late, the research in this field has grown rapidly. The study provides a mapping of top journals and authors, works of greatest impact and of co-authorship, co-citation and bibliographic coupling networks, which evidence the low intensity of researcher's interactions and scientific production dispersion in the field. The main subjects found in the sharing economy literature are determinants, motivations and barriers, sharing economy impacts, regulation, models and frameworks, critical approach and entrepreneurship and sharing-based new businesses. Research limitations/implications: The analyses did not take into account the timing perspective. Further research could undertake a timeline-based approach in order to present direct citation networks and to relate works according to the year when they were published. Originality/value: The study innovates by identifying the main subjects in the sharing economy literature, as well as by presenting network analysis for some bibliometric indicators, complementing previous research in the field.